Evaluating Incorporation of Drug Restrictions into Computerized Drug Order Entries after Transition to an Electronic Health Record. Issue 7 (July 2013) - Rodriguez, Ryan; Staley, Benjamin; Hatton, Randy C.
Background: Incorporation of drug restriction policy into electronic drug order entries (DOEs) can promote responsible medication use and resource utilization when implemented systematically. Objective: To identify drugs that require further incorporation of formulary restriction policy into their DOEs after migration to an electronic health record with computerized prescriber order entry (CPOE). Methods: After transition to CPOE, test orders for formulary restricted drugs were entered in the CPOE environment. Data were collected about rationale for drug restriction, type of formulary restriction, presence of incorporation of restriction policy into the DOE, and whether incorporation was consistent with a recommended method. Restricted drugs requiring revision of policy incorporation into their DOEs were analyzed to create a prioritized task list based on rationale for the restriction. Results: Of all restricted drugs, 63.6% (287/451) did not have restriction policy incorporated into their DOEs consistent with the recommended method and therefore required revision. Eighteen percent (81/451) of restricted drugs had no incorporation of restriction policy in their DOEs. Safety was the rationale for restriction in 21% (17/81) of these, which received highest priority for revision. When drugs were orderable but restricted, 61.9% (78/126) lacked optimal incorporation of policy in DOEs to promote adherence. When drugs were not orderable, 64% (206/322) did not provide guidance to formulary alternatives in DOEs when they should have. Conclusion: After transition to CPOE, almost two-thirds of all analyzed restricted drugs lacked optimal incorporation of formulary restriction policies in their DOEs. DOEs with restrictions related to safety reasons were among those most frequently requiring revision. Some DOEs can better promote adherence and provide guidance to prescribers through revision. Predefined, systematic implementation strategies should be used during changes in computerized drug use processes.